2017
DOI: 10.1111/jgs.14921
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Women's Awareness of and Reasons for Lack of Postfracture Osteoporotic Care

Abstract: These findings suggest low awareness about OP and its contribution to fracture risk, lack of understanding about the benefits of pharmacotherapy, and limited discussion about OP with primary care physicians. Information about individual's beliefs and knowledge gaps can help design targeted patient and provider education to improve treatment rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…(25) Furthermore, because of the expense of long-term care in the US, 80% of those patients became destitute. (32) Thus, they are not likely to take appropriate steps to address their risk. (25,31) Most patients do not realize that they are at risk for another fracture, that osteoporosis caused their fracture, and that interventions can reduce their risk.…”
Section: Fundamental Recommendations and Rationalesmentioning
confidence: 99%
See 2 more Smart Citations
“…(25) Furthermore, because of the expense of long-term care in the US, 80% of those patients became destitute. (32) Thus, they are not likely to take appropriate steps to address their risk. (25,31) Most patients do not realize that they are at risk for another fracture, that osteoporosis caused their fracture, and that interventions can reduce their risk.…”
Section: Fundamental Recommendations and Rationalesmentioning
confidence: 99%
“…(25,31) Most patients do not realize that they are at risk for another fracture, that osteoporosis caused their fracture, and that interventions can reduce their risk. (32) Thus, they are not likely to take appropriate steps to address their risk. (33) To communicate riskrelated messages effectively, all health care professionals should provide consistent and sustained messaging throughout the care pathway, beginning at time of diagnosis and continuing repeatedly.…”
Section: Fundamental Recommendations and Rationalesmentioning
confidence: 99%
See 1 more Smart Citation
“…A Medicare analysis of 145,185 individuals with a fragility fracture found that only 30% received treatment over 12 months following the fracture, whereas a survey of women with a prior fracture estimated that the rate could be as low as 16%. () In order for the previous gains seen in fracture prevention to continue, preventive measures and therapies must be utilized effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of primary care expertise, practitioners cannot compel patients to report for DXA or initiate pharmacotherapy if patients do not attribute fracture to osteoporosis or consider osteoporosis to be a significant health concern, a phenomenon noted by others. 52,53 While participants in these studies on the whole were receptive to DXA and many had undergone post-fracture imaging, they demonstrated limited knowledge of DXA and its role in bone health management. Poor patient knowledge is compounded by reported inconsistent provider messaging and misinformation, reinforcing a point made by others regarding the importance of clinical ownership of bone health care.…”
Section: The Role Of Primary Care In Engaging Patient Use Of Dxamentioning
confidence: 99%